A percepção da idéia de justiça em um contexto de mudanças organizacionais. - Oliveira, Norma Suely Christiano de (2004)
This thesis aims to analyse the perception of justice in the day-to-day of the corporations, when organizational changes take the place therein. The context of the corporation which is focused herein derives from the globalization of the Brazilian market of telecommunications which has been started in the 90`s. Two substantial changes have occurred in the period of only ten years. What happens in the day-to-day of the corporations in those moments, when a deep change in their structures is operated? Which is the impact of such change in the working hours and in the internal relations? Those questions have been relevant to and have motivated the perfomance of the survey. It has been developed with twenty employees of the ¿Z¿ corporation, who are based in the city of Rio de Janeiro and who have been heard. Such different interviews with the employees have reached thirty hours. After the completion of the due analysis of the contents of the survey, this thesis sustains that the organizational practices of the ¿Z¿ corporation do not adhere to modernization and, therefore lead the perception of the unfair. This thesis wishes to contribute to the field of the organizational studies, with an interpretation of the data that have been compiled in a given moment, about a corporation.